2018
DOI: 10.1017/dmp.2018.84
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health of Gulf Coast Residents 6 Years After the Deepwater Horizon Oil Spill: The Role of Trauma History

Abstract: ObjectiveThe purpose of this study was to examine the associations between oil spill exposure, trauma history, and behavioral health 6 years after the Deepwater Horizon oil spill (DHOS). We hypothesized that prior trauma would exacerbate the relationship between oil spill exposure and behavioral health problems.MethodsThe sample included 2,520 randomly selected adults in coastal areas along the Gulf of Mexico. Participants reported their level of oil spill exposure, trauma history, depression, anxiety/worry, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Like foods, you can't eat certain foods because it can—it can trigger an attack. Or trigger an allergy outbreak, or eczema … it impacts economically all around the board.”These conversations overlapped with other discussions around personal health and health care access and may be examples of spill‐related illness anxiety (Ayer et al, 2018). Because many participants who described out‐of‐pocket costs also experienced uncertainty about the source of the allergy or illness, the cost of these expenses could be interpreted as both financial and emotional.…”
Section: Resultsmentioning
confidence: 87%
“…Like foods, you can't eat certain foods because it can—it can trigger an attack. Or trigger an allergy outbreak, or eczema … it impacts economically all around the board.”These conversations overlapped with other discussions around personal health and health care access and may be examples of spill‐related illness anxiety (Ayer et al, 2018). Because many participants who described out‐of‐pocket costs also experienced uncertainty about the source of the allergy or illness, the cost of these expenses could be interpreted as both financial and emotional.…”
Section: Resultsmentioning
confidence: 87%
“…Cope and Slack used county-level demographic data and socioeconomic status to calculate an index of place-based social vulnerability developed by Cutter et al (2003) called the Social Vulnerability Index. Ayer et al (2019) hypothesized that exposure to DWH would be related to depression, anxiety, alcohol abuse, and illness anxiety (defined by Ayer et al, 2019, p. 2) as "excessive concern or worry about having or getting a serious illness") 6 years post spill. Vulnerable populations were found to have increased psychological stress after the DWH spill (Cope et al, 2013;Lee & Blanchard, 2012), but researchers found that strong community attachment was connected to better outcomes for families, increased individual well-being, and positive mental and physical health outcomes (Cope et al, 2013), but this may not hold for all situations.…”
Section: Psychosocial Studiesmentioning
confidence: 99%
“…The DWH spill has been a long-lasting life event for residents of the GOM, disrupting routine behavior, increasing anxiety, straining economic resources, and negatively affecting mental health (Ayer et al, 2019). Those employed in, and dependent upon, the oil and fishing industries were particularly vulnerable, suffering disproportionately during and after the disaster (Ayer et al, 2019;Cope et al, 2013;Cope et al, 2016;Lee & Blanchard, 2012;Parks et al, 2017).…”
Section: Psychosocial Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With funding from the National Science Foundation, we built on a survey we fielded after the 2010 Deepwater Horizon oil spill and followed up with the same participants. 2,3 But these examples are the exception, not the rule; predisaster survey data are rarely available and even more rarely planned. This lack of a pre-post comparison fundamentally limits the quantification of a disaster's human toll and stands in stark contrast to our ability to assess infrastructure and other damage.…”
mentioning
confidence: 99%